Reducing stroke burden through a targeted self-management intervention for reducing stroke risk factors in high-risk Ugandans: A protocol for a randomized controlled trial - Kaddumukasa, Mark; Najjuma, Josephine; Mbalinda, Scovia Nalugo; Kaddumukasa, Martin N.; Nakibuuka, Jane; Burant, Christopher; Moore, Shirley; Blixen, Carol; Katabira, Elly T.; Sajatovic, Martha (Plos one, 2021)
Introduction: Stroke burden is rapidly increasing globally. Modifiable risk factors offer an opportunity to intervene, and targeting hypertension is a key actionable target for stroke risk reduction in sub-Saharan Africa. This 3-site planned randomized controlled trial builds on promising preliminary data. Methods: A total of 246 Ugandan adults will be recruited randomized to experimental intervention vs. enhanced treatment control. Intervention participants will receive six weekly group-format stroke risk reduction self-management training sessions, and the controls will receive information on cardiovascular risk. The primary study outcome is systolic B.P. measured at baseline, 13-week, 24 weeks (6 months). Secondary outcomes include other biological and behavioral stroke risk factors. Discussion: The curriculum-guided self-management Targeted Management Intervention (TEAM) program is anticipated to reduce the stroke burden in Uganda.
Keywords: Stroke burden; Self-management; High-risk Ugandans; Sub-Saharan Africa